Proceedings of 11th International Conference on Ion Implantation Technology
DOI: 10.1109/iit.1996.586283
|View full text |Cite
|
Sign up to set email alerts
|

Production proven electrostatic platen for medium current implantation

Abstract: Abstra,ct-Electrostatic wafer platens (ESPs) for ion implant systems offer enormous benefits in manufacturing productivity. This paper describes and compares the performance of the standard clamp in current use in more than 50 user sites with a new cooled platen design. As would be expected the ESP platens do not affect dosing, charging, or front side particulates. Device damage from the ESP is not an issue because of the safe AC operating mode. Cooling performance of 1 watt/cm* for 200mm wafers using nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies of back side defectivity have been previously reported in the literature. [1][2][3][4][5][6][7][8][9][10] The majority of processing equipment for IC devices utilize single wafer processing for Etch, Photolithography, CVD, PECVD, and Polish operations. Yet, Diffusion and Wet Clean processes are typically performed in batches and are susceptible to defect transfer between wafers during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of back side defectivity have been previously reported in the literature. [1][2][3][4][5][6][7][8][9][10] The majority of processing equipment for IC devices utilize single wafer processing for Etch, Photolithography, CVD, PECVD, and Polish operations. Yet, Diffusion and Wet Clean processes are typically performed in batches and are susceptible to defect transfer between wafers during processing.…”
Section: Introductionmentioning
confidence: 99%